Why Arab society wants to take Turkish democracy as model?: social analysis of the resistant movements. - Kayadibi, Saim; Birekul, Mehmet (2011)
In retrospect, and having witnessed the “Arab Spring” of the Middle East, we see today that the Muslim countries in this land are displaying significant social changes. Here, it is a noteworthy point that the changes taking place in Turkey in this transformation is more peaceful and less damaging to the society in contrast to the Arab world. Of course, it could be said that the reason for Turkey’s transformation became bloodless is because of the comprehension of democracy and the existence of democratic elections which contrary to the Arab world. Another noteworthy point here is that the resistant movements’ moving point in the Arab world is willing to take a single democratic and secular state Turkey in the region as a model. In particular, it could be said that increasing of the rhetoric and the discussion of this model effectively in the Arab world is because of the influence of the overwhelming support of conservatives of AK Party (Justice and Development Party) led by Recep Tayyip Erdoğan. Today, the wave of resistance starting from Tunisia to Egypt, Libya and Syria which has influenced almost all the Muslim land that has made Turkey more popular in their agendas. The Turkish society, which internalized democracy within the process of 50 years experience, is trying to keep the debate of advanced democracy while it is closely monitoring the developments in the Arab world. This paper analysis the role of Turkey as democratic country to give inspiration to the social resistant movements in the Arab world; the declarations of the leaders and the opinion of the peoples in these countries are evaluated through the media and publications; inferences shall be given on Turkey as model and the reality of the Middle East. Keywords: Democratic Election; Turkish Democracy; Arab Spring; Resistant Movements; AK Party.